SISTEM PERLINDUNGAN UPAH DI INDONESIA - Evy Savitri Gani (IAIN Ambon, 2017)
Wages are very important for the workers or laborers. Wage workers or laborers can meet their needs. Importance of wages also followed with a complex problem. One of the problems of wages that employers or employers who do not pay wages in accordance with existing regulations, its becaused workers as the weaker party by employers. Government as the most important preformance working relationships required to protect workers as the weaker party. Therefore in Law No. 13 of 2003 on employment set wage policy that protects the interests of workers or laborers, among others, about the minimum wage, overtime, wages do not come to work because of something, and others. All the above remuneration shall be implemented by employers and the government must watch so as to create a good wage sistem. Keywords: wages, laborer.